The linker region in receptor guanylyl cyclases is a key regulatory module: mutational analysis of guanylyl cyclase C - Saha, Sayanti; Biswas, Kabir Hassan; Kondapalli, Chandana; Isloor, Nishitha; Visweswariah, Sandhya S (The Journal of biological chemistry, 2009)
Receptor guanylyl cyclases are multidomain proteins, and ligand binding to the extracellular domain increases the levels of intracellular cGMP. The intracellular domain of these receptors is composed of a kinase homology domain (KHD), a linker of approximately 70 amino acids, followed by the C-terminal guanylyl cyclase domain. Mechanisms by which these receptors are allosterically regulated by ligand binding to the extracellular domain and ATP binding to the KHD are not completely understood. Here we examine the role of the linker region in receptor guanylyl cyclases by a series of point mutations in receptor guanylyl cyclase C. The linker region is predicted to adopt a coiled coil structure and aid in dimerization, but we find that the effects of mutations neither follow a pattern predicted for a coiled coil peptide nor abrogate dimerization. Importantly, this region is critical for repressing the guanylyl cyclase activity of the receptor in the absence of ligand and permitting ligand-mediated activation of the cyclase domain. Mutant receptors with high basal guanylyl cyclase activity show no further activation in the presence of non-ionic detergents, suggesting that hydrophobic interactions in the basal and inactive conformation of the guanylyl cyclase domain are disrupted by mutation. Equivalent mutations in the linker region of guanylyl cyclase A also elevated the basal activity and abolished ligand- and detergent-mediated activation. We, therefore, have defined a key regulatory role for the linker region of receptor guanylyl cyclases which serves as a transducer of information from the extracellular domain via the KHD to the catalytic domain.